2014
DOI: 10.1038/srep05991
|View full text |Cite
|
Sign up to set email alerts
|

Inverse Pseudo Hall-Petch Relation in Polycrystalline Graphene

Abstract: Understanding the grain size-dependent failure behavior of polycrystalline graphene is important for its applications both structurally and functionally. Here we perform molecular dynamics simulations to study the failure behavior of polycrystalline graphene by varying both grain size and distribution. We show that polycrystalline graphene fails in a brittle mode and grain boundary junctions serve as the crack nucleation sites. We also show that its breaking strength and average grain size follow an inverse ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
77
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(87 citation statements)
references
References 39 publications
9
77
1
Order By: Relevance
“…b Pseudo Hall-Petch strength reduction in polycrystalline graphene (Song et al 2013a). c Inverse pseudo Hall-Petch relation in polycrystalline graphene (Sha et al 2014b). Reprinted from Kotakoski and Meyer (2012) and Song et al (2013a) with permission grains, but the strength increases as the grain size is reduced, similar to the classical Hall-Patch relation in polycrystalline metals.…”
Section: Theoretical Strength Of Graphenementioning
confidence: 80%
See 2 more Smart Citations
“…b Pseudo Hall-Petch strength reduction in polycrystalline graphene (Song et al 2013a). c Inverse pseudo Hall-Petch relation in polycrystalline graphene (Sha et al 2014b). Reprinted from Kotakoski and Meyer (2012) and Song et al (2013a) with permission grains, but the strength increases as the grain size is reduced, similar to the classical Hall-Patch relation in polycrystalline metals.…”
Section: Theoretical Strength Of Graphenementioning
confidence: 80%
“…Considerable attention has been attracted to possible grain size effect on the strength of polycrystalline graphene (Kotakoski and Meyer 2012;Song et al 2013a;Sha et al 2014b;Yang et al 2015b). Figure 7 shows that there exist apparent discrepancies or controversies in the observed grain size dependent strength of polycrystalline graphene in the literature.…”
Section: Theoretical Strength Of Graphenementioning
confidence: 99%
See 1 more Smart Citation
“…However, those findings are in contrast to theory taking into account more natural GB geometries. Such simulations typically result in lower values for E 3D [90][91][92][93][94][95]. In particular, Kotakoski and Meyer [90], who performed large-scale MD simulations on polycrystalline graphene, found significantly lower values of the Young's modulus E 600 GPa…”
Section: Dmentioning
confidence: 99%
“…The dependence of fracture strength on grain size for the studies in [91][92][93]95] are shown in figure 5. Notably, three studies [92,93,95] report increasing strength with increasing grain size, while Song et al [91] find the opposite trend. The fracture strengths in the study by Kotakoski and Meyer [90] and the paper of Yang et al [94], however, showed no significant dependence on grain size.…”
Section: Fracture Strengthmentioning
confidence: 99%